Should Researchers Offer Results to Family Members of Cancer Biobank Participants? A Mixed-Methods Study of Proband and Family Preferences. Issue 1 (2nd January 2019) - Gordon, Deborah R.; Radecki Breitkopf, Carmen; Robinson, Marguerite; Petersen, Wesley O.; Egginton, Jason S.; Chaffee, Kari G.; Petersen, Gloria M.; Wolf, Susan M.; Koenig, Barbara A.
Abstract: Background: Genomic analysis may reveal both primary and secondary findings with direct relevance to the health of probands' biological relatives. Researchers question their obligations to return findings not only to participants but also to family members. Given the social value of privacy protection, should researchers offer a proband's results to family members, including after the proband's death?Methods: Preferences were elicited using interviews and a survey. Respondents included probands from two pancreatic cancer research resources, plus biological and nonbiological family members. Hypothetical scenarios based on actual research findings from the two cancer research resources were presented; participants were asked return of results preferences and justifications. Interview transcripts were coded and analyzed; survey data were analyzed descriptively.Results: Fifty-one individuals (17 probands, 21 biological relatives, 13 spouses/partners) were interviewed. Subsequently, a mailed survey was returned by 464 probands, 1, 040 biological family members, and 399 spouses/partners. This analysis highlights the interviews, augmented by survey findings. Probands and family members attribute great predictive power and lifesaving potential to genomic information. A majority hold that a proband's genomic results relevant to family members' health ought to be offered. While informants endorse each individual's choice whether to learn results, most express a strong moral responsibility to know and to share, particularly with the younger generation. Most have few concerns about sharing genetic information within the family; rather, their concerns focus on the health consequences of not sharing.Conclusions: Although additional studies in diverse populations are needed, policies governing return of genomic results should consider how families understand genomic data, how they value confidentiality within the family, and whether they endorse an ethics of sharing. A focus on respect for individual privacy—without attention to how the broad social and cultural context shapes preferences within families—cannot be the sole foundation of policy.